Carbon Taxes within the Context of the European Green Deal - Boneva, Svetla (Research Papers, 2021)
The objective of the research is to present the importance of the carbon taxes within the context of the European green deal. For the achievement of this objective two basic research tasks have been fulfilled: 1.) the importance of carbon taxation within the current development of the European Union has been analyzed; 2.) the main authors and research directions regarding carbon taxes as a type of environmental taxes have been generalized and discussed. The research methods used in the study involve elements of retrospective analysis, comparative and content analysis and generalizations of the main ideas of key strategic and regulatory documents in this research field. The results of the research are generalizations and analyses providing solid ground for taking evidence-based decisions regarding future carbon taxes introduction at national and EU level as well as for addressing motivated recommendations towards the application of this type of taxes.
Keywords: Carbon taxes; European green deal